(untitled) (Nuntius Antiquus, 2017)
It is well known among classicists – and a matter of rare agreement – that the Roman poet Quintus Horatius Flaccus (Horace) is a great ironist. His poetry is full of double meanings, self mockery and deceptions; but one could ask what happens (or what is performed) when we are facing irony’s edge in political terms. In such a case, the book of Epodes, published a few years after the Battle of Actium (31 BC), may well serve as perfect example of how a poetic book could be able to present a complex political project through the meanders of irony. In order to accomplish that reading, I will analyze here the first 7 epodes with emphasis on the last one.